Evaluating 5 decades of atmospheric 85Kr measurements in the southern hemisphere to derive an input function for dating water and ice with implications for interhemispheric circulation and the global 85Kr emission inventory - Kersting, Arne; Schlosser, Clemens; Bollhöfer, Andreas; Suckow, Axel (Journal of environmental radioactivity, 2020)
In July 2015, the currently only active monitoring station for atmospheric 85Kr measurements in the southern hemisphere went operational at the Commonwealth Scientific and Industrial Research Organization (CSIRO) in Adelaide, Australia. Here, this new data is presented and combined with measurements from historic monitoring stations, to generate a85Kr input function for the southern hemisphere which is crucial for the application of 85Kr as a dating tracer for water and ice. After a linear increase in atmospheric 85Kr concentrations between 1980 and 2005, concentrations stabilized yielding mean 85Kr activity concentration during the Adelaide monitoring period of 1.3 ± 0.15 Bq/m³ air with slight variations indicating seasonal effects. Data from three northern hemispheric monitoring stations Schauinsland, Freiburg and Jungfraujoch of the German Federal Office for Radiation Protection (BfS), located in Central Europe are used to calculate an interhemispheric exchange time of 1.25 ± 0.24 years, using a simple box model approach. Furthermore, it is investigated whether a southern hemispheric 85Kr input function can be calculated from the baseline of the northern hemispheric data set. A comparison between the calculated and the fitted input function shows that analytical techniques can just resolve the concentration differences, emphasising the need of southern hemispheric monitoring stations for 85Kr. Analysing the decay-corrected input function and taking the current detection limit of low-level counting and Atom Trap Trace Analysis of 0.05 Bq/m³ air, a maximum apparent 85Kr tracer age of 40 years can be determined in the southern hemisphere. Finally, the 85Kr measurements are used to derive global 85Kr emission rates which are found to be in good agreement with published emissions from nuclear reprocessing plants.
Die Zahl "85" ist im Titel hochgestellt
Gesehen am 17.02.2022